Case Report: Osteogenesis Imperfecta in Daughter Patients Aged 6 Years 9 Months - Kirnia Tri Wulandari; Tikto Tikto (Eduvest - Journal of Universal Studies, 2021)
Osteogenesis imperfecta (OI) is a rare disease with a wide spectrum of clinical and genetic variability; It is characterized by very brittle bones, blue sclera, dentinogenesis imperfecta, scoliosis and hearing loss. This study aims to identify and report cases of osteogenesis imperfecta in child patients aged 6 years 9 months. This study uses a qualitative method with the type of case report. The sampling technique used in this study is random sampling technique by Slovin formula in Husein Umar. In this study, each population has same opportunity to be selected as a sample. Based on the results of the analysis and discussion, it can be concluded that the case of osteogenesis imperfecta is a complex congenital disorder and must be distinguished from other differential diagnoses. Furthermore, with a careful examination, it is hoped that the diagnosis of osteogenesis imperfecta cases can be better.